Konflik Rumah Tangga Pada Wanita Peran Ganda (Studi Deskriptif Pada Wanita Yang Mengalami Perceraian Di Desa Rowotengah) - Khulasi, Balqis Al; Devi, Linda Meilisa; Wahida, Nur; Fitriana, Ani Qotus Zuhro’ (CV. ITTC INDONESIA, 2022)
Abstract Conflicts that occur in the household can be a major factor that results in divorce. Divorce has had a huge impact on women's lives, not a few women who end up having to become the backbone of their families to meet the needs of their children. The existence of two roles that must be carried out by a woman is what is called a dual role woman. The purpose of this study was to see a more concrete picture and phenomenon related to domestic conflicts experienced by women with dual roles in Rowotengah village, where one of these problems was regarding disputes and constant bickering which resulted in divorce. This research uses a qualitative method with a descriptive study type of research. The results of the study show that most of the conflicts that occur are due to different perspectives between husbands and wives which lead to divorce. The conflict experienced by women with dual roles after divorce is getting hate speech from people around them, tending to be sensitive and emotional, and pressure from the surrounding environment because they become the subject of conversation.